The use of amino acids as bioactive substance: a strategy to increase yield in summer arugula (Eruca sativa L. Mill) crops - Dovis, Veronica Lorena; Andrade, Bruna Batista; Redondo, Simone Ungari Azzolino; Erismann, Norma de Magalhães (Comunicata Scientiae, 2024)
Foliar application of amino acids can assist crops to maintain homeostasis under diurnal temperature variations and excessive solar irradiance. The objectives of this study were to investigate the effects of the organic fraction and mineral nutrients of an amino acid solution on arugula plants and the effects of weekly applications of this solution on their growth and biomass yield. Two experiments were conducted in a completely randomized design, in a greenhouse (Experiment 1) and on open-field benches (Experiment 2), in Iracemápolis, SP, Brazil. Experiment 1 consisted of foliar applications of water (control), a solution containing 59 and 40.9 g ha-1 of nitrogen and sulfur, respectively (N+S), and a solution containing 85 g ha-1 of amino acids, with seven replications. Experiment 2 consisted of four different number (0, 1, 2, and 3) of weekly foliar applications of 85 g ha-1 of amino acids, with six replications. Chlorophyll a fluorescence, chlorophyll and carotenoid contents, and fresh and dry biomass weights were evaluated in both experiments. In Experiment 1, shoot fresh weight of plants treated with amino acids increased by 21% and 6% compared to those in the control and N+S treatment, respectively. Amino acid application increased chlorophyll and carotenoid contents, improving photosynthetic performance by increasing effective quantum efficiency of photosystem II and photochemical quenching. In Experiment 2, weekly application of 85 g ha-1 of amino acids increased shoot fresh weight by approximately 10% per application. Therefore, foliar application of amino acids can increase fresh biomass of arugula plants grown under both mild and warmer climate conditions.